A click chemistry amplified nanopore assay for ultrasensitive quantification of HIV-1 p24 antigen in clinical samples - Xiaojun Wei; Xiaoqin Wang; Zehui Zhang; Yuanyuan Luo; Zixin Wang; Wen Xiong; Piyush K. Jain; John R. Monnier; Hui Wang; Tony Y. Hu; Chuanbing Tang; Helmut Albrecht; et al. (Nature Communications, 2022)
Accurate detection of antigen p24 for HIV−1 early diagnosis remains challenging. Here the authors present a click chemistry amplified nanopore (CAN) assay that allows p24 quantification at ultralow concentration range in clinical samples.